Correlation of Serum Ferritin and Liver Enzymes In Thalassemia Major Children (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Worldwide, thalassemia is the most prevalent gene defect. The main treatment of thalassemia is the blood transfusion along with chelation therapy. Repeated blood transfusions leads to iron overload along with chelation therapy detoriates liver function. This study aims to see the correlation between liver enzymes with serum ferritin in children with b-thalassemia major.  Materials and methods: From Chattogram Medical College Hospital 79 children suffering from thalassemia major in the age group of 5-12 years who received regular blood transfusions and iron chelators were included in this cross sectional study. Serum ferritin and liver enzymes [Alanine Transaminase (ALT) Aspartate Transaminases  (AST) Alkaline Phosphatase (ALP) and Gamma  Glutamyltransfarase (GGT)] were tested and their correlation was assessed. Pearson sbivariate correlation coefficient was used to determine the correlation.Results: The mean age was 8.5±2.4 years and 57% were male. The mean age at diagnosis of thalassemia was 10.7±4.2 months and mean number of transfusion was90±29 and ranged between 40-140 transfusions. All of the children were on oral ironchelation therapy and the average age of initiation chelation therapy was 5.7±1.1years. Sixty-four (81%) children had growth retardation. Mean serum ferritin level was 3740.7±2184.8ng/ml and only 3.8% of the patients had serum ferritin level